2018
DOI: 10.5812/ijem.12104
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Osteoporosis Pharmacotherapy Fracture Rates: Analysis of a MarketScan® Claims Database Cohort

Abstract: BackgroundSeveral different classes of medications have been shown to be efficacious at preventing fractures in patients with osteoporosis. No study has compared real world efficacy at preventing fractures between all currently approved medications.ObjectivesTo directly compare the efficacy of all currently available osteoporosis medications by using a large population claims database.MethodsThe Truven Health Analytics MarketScan® database from 2008 - 2012 was used to identify all patients who started a new os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…Overall, the incidence of fractures more than doubled in patients ≥ 65 versus < 65 years old. In general, the lower rates of fractures observed in the present study compared to previously published results from observational studies are consistent with the relatively young age of the studied population [24][25][26]. Indeed, in a study using claims data from commercially insured patients (all patients < 65 years old; mean age: 56.0 years old), the authors estimated incidence rates of fractures at any site between 15.4 and 16.1 per 1,000 patient-years for bisphosphonates [25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, the incidence of fractures more than doubled in patients ≥ 65 versus < 65 years old. In general, the lower rates of fractures observed in the present study compared to previously published results from observational studies are consistent with the relatively young age of the studied population [24][25][26]. Indeed, in a study using claims data from commercially insured patients (all patients < 65 years old; mean age: 56.0 years old), the authors estimated incidence rates of fractures at any site between 15.4 and 16.1 per 1,000 patient-years for bisphosphonates [25].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, in a study using claims data from commercially insured patients (all patients < 65 years old; mean age: 56.0 years old), the authors estimated incidence rates of fractures at any site between 15.4 and 16.1 per 1,000 patient-years for bisphosphonates [ 25 ]. In a similar study using claims from Medicare insured patients (all patients ≥ 65 years old; mean age, 78.2 years old), the authors estimated at 56.3 per 1,000 patient-years the incidence rate of fractures at any site [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, given this was a noninferiority trial powered for a different primary outcome [9], the study did not have sufficient power to detect significant differences in fracture rates. While head-to-head comparisons of GR risedronate versus IR risedronate or alendronate are lacking, our estimates are roughly aligned with estimates from studies that reported fracture rates for oral bisphosphonates (the unadjusted risks for any fracture were 50.6-66.8 fracture events per 1000 women-years in the current sample vs. 15-81 fracture events per 1000 women-years in other studies [6,[34][35][36][37][38]; unadjusted risks for site-specific fractures: 3.4-27.4 vs. 3-14 fracture events per 1000 womenyears, respectively [34,38]).…”
Section: Discussionsupporting
confidence: 78%
“…This database has been used extensively in the field of orthopaedics in analyses of costs and spending. 3 , 19 , 25 …”
Section: Methodsmentioning
confidence: 99%